A serological assay to detect SARS-CoV-2 seroconversion in humans - Amanat, Fatima; Stadlbauer, Daniel; Strohmeier, Shirin; Nguyen, Thi H. O.; Chromikova, Veronika; McMahon, Meagan; Jiang, Kaijun; Arunkumar, Guha Asthagiri; Jurczyszak, Denise; Polanco, Jose; Bermudez-Gonzalez, Maria; Kleiner, Giulio; et al. (Nature medicine, 2020)
Here, we describe a serological enzyme-linked immunosorbent assay for the screening and identification of human SARS-CoV-2 seroconverters. This assay does not require the handling of infectious virus, can be adjusted to detect different antibody types in serum and plasma and is amenable to scaling. Serological assays are of critical importance to help define previous exposure to SARS-CoV-2 in populations, identify highly reactive human donors for convalescent plasma therapy and investigate correlates of protection. Development of an enzyme-linked immunosorbent assay to detect antibodies to the SARS-CoV-2 spike protein in human sera and plasma.